Pengaruh Content Marketing, Live Streaming dan Flash Sale terhadap Impulse Buying pada Pengguna Aplikasi Tiktok Shop di Surabaya: Studi pada Pengguna Tahun 2022-2023 - Kurniawan, Rafika Athiyah; Nugroho, Rusdi Hidayat (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The presence of the internet is necessary for businesses, which makes it an important platform for modern sales and marketing. TikTok is often an efficient social media platform for online marketing. The purpose of this study is to determine the effect of content marketing, live streaming, flash sales on impulse buying in TikTok Shop application users in Surabaya. The type of research used is quantitative research. The population in this study were all TikTok Shop application users in 2022 to 2023 who live in Surabaya using a sample of 200 respondents. The sampling method used is non probability sampling and the sampling technique is purposive sampling. Multiple linear regression analysis was applied to analyze the data tested with SPSS version 25. The results of this study state that content marketing, live streaming, and flash sales have a significant effect on impulse buying. Content marketing, live streaming, and flash sale variables are valid and reliable variables. Simultaneously, the variables of content marketing, live streaming and flash have a positive and significant effect on impulse buying. Partially, content marketing and flash variables have a positive and significant effect on impulse buying. While the flash sale variable has no effect on impulse buying